1984
DOI: 10.1002/tera.1420290106
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the route of administration for genetic differences in benzo[a]pyrene‐induced in utero toxicity and teratogenicity

Abstract: C57BL/6N (Ahb/Ahb) mice have a high‐affinity Ah receptor in tissues, whereas AKR/J and DBA/2N (Ahd/Ahd) mice have a poor‐affinity Ah receptor. The cytochrome P1‐450 induction response (enhanced benzo[a]pyrene metabolism) occurs much more readily in Ahb/Ahb and Ahb/Ahd than in Ahd/Ahd mice, at any given dose of the inducer benzo[a]pyrene. Embryos from the AKR/J × (C57BL/6N)(AKR/J)F1 and the reciprocal backcross were studied during benzo[a]pyrene feeding of the pregnant females. Oral benzo[a]pyrene (120 mg/kg/da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…Thus, it appears that the induced SCE frequency in mice in vivo is influenced by genetic differences not only in drug activation but also in drug detoxication or absorption. For example, oral administration of benzo[a]pyrene to nonresponsive pregnant mice leads to greater embryotoxicity in nonresponsive embryos than in responsive embryos, which is the opposite of the results obtained after intraperitoneal administration (7,(31)(32)(33).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, it appears that the induced SCE frequency in mice in vivo is influenced by genetic differences not only in drug activation but also in drug detoxication or absorption. For example, oral administration of benzo[a]pyrene to nonresponsive pregnant mice leads to greater embryotoxicity in nonresponsive embryos than in responsive embryos, which is the opposite of the results obtained after intraperitoneal administration (7,(31)(32)(33).…”
Section: Resultsmentioning
confidence: 90%
“…However, there is no detectable activity of the phenobarbital-induced cytochrome P-450 system (not associated with the Ah locus) in 9-day rat embryos (42) or in cultured rat yolk sac cells (43). Furthermore, predominance of quinone formation in mouse embryos treated with benzo[a]pyrene at 4 days of gestation (9) or at 10 days of gestation (33) suggests that detoxication enzymes are relatively inactive at early stages of development. Metabolism of benzo[a]pyrene by cytochrome P-450-mediated oxidation is thus the only system known to be active very early in gestation.…”
Section: Resultsmentioning
confidence: 99%
“…In animal experiments, PAHs have been consistently shown to be teratogenic. The embryonic development of fish embryos was disturbed (20), and congenital malformations of various organ systems were induced by benzo(a) pyrene exposure to pregnant mice (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being genotoxic and carcinogenic, PAHs such as BaP are endocrine disruptors (Bostrom et al 2002;Bui et al 1986;Davis et al 1993). Prior laboratory and two human studies in Central Europe indicate that transplacental exposure to PAHs at relatively high concentrations (annual average airborne concentrations of 7-17 ng/m 3 BaP in the human studies) is associated with adverse birth outcomes (Barbieri et al 1986;Bui et al 1986;Dejmek et al 2000;Legraverend et al 1984;Perera et al 1998). We recently reported that prenatal PAH exposure estimated by personal air monitoring was associated with reduced birth weight and head circumference among African Americans in the present New York City, New York, cohort (Perera at al.…”
mentioning
confidence: 99%